ARTICULACAO TEMPOROMANDIBULAR: TRATAMENTO IMEDIATO DA SINDROME DOLOROSA - Lima De Castro, A.; Garrafa, V.; Adhemar Furuse, T. (My University, 1973)
Brilliant Green (BG) agar and Hektoen enteric (HE) agar media were compared for their efficiency in isolating salmonellae from various food products. Of the 11,226 food specimens examined, 1,662 (or 14.9%) yielded salmonellae. Of this number, 1,475 (88.7%) were recovered from BG agar and 1,315 (79.1%) were recovered from HE agar media. The results indicate that BG agar is more effective in isolating salmonellae from food products. A smaller subsidiary study showed HE agar to be more selective than BG agar. Four hundred ten specimens yielded 92 nonlactose fermenting isolants other than salmonellae on BG agar and only 11 such isolants on HE agar.
Temporomandibular joint: immediate treatment of the painful syndrome